Perception on Investing in Stocks With ESG Relevance: A Descriptive View on Influence of Key Demographic Variables and Risk Profiling of Investors - R Satish; S Saravanan; N. V. Ramachandran (EAI Endorsed Transactions on Energy Web, 2023)
INTRODUCTION: To be purposeful beyond the return consideration by the way of giving importance to environment, society and governance of company through investing in companies that give priority to aforementioned factors by investors and their perception towards ESG is the crux of this research paper. For this several factors that measures the environment, social and governance are itemized and considered as the dependent variable.